The Study of Extrakuricular Karate Evaluation Towards Achievement of Students Karate (Department of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this research is to figure out the development of karate extracurricular in SMA N 1 Slawi, SMA N 2 Slawi and SMA N 1 Bojong. This is a qualitative research with percentage descriptive approach. The result shows that there are some disadvantages in the development of karate exracuriccular so that the student’s karate achievement in Tegal Regency is not maximum. First, there is no selection for athletes. Second, the programs for training have not been implemented well. Also the coaches do not have legal certificate. Third, the infrastructures for karate have not supported the athlete’s achievement yet. Fourth, the management of karate organization does not run well. The last, karate extraxurricular does not get enough funds to support their activities. Based on the data obtained from the research, it can be concluded that there are some constraints which hamper the efforts to get higher achievement in karate.